Electrochemical Properties of Robson Type Macrocyclic Dicopper(II) Complexes - Alegria,Elisabete C. B. A. (2015)
The redox properties of the 1,10-phenanthroline containing Robson type symmetrical macrocyclic dicopper(II) complex [Cu2L(H2O.phen)2](ClO4)2 1 (L = μ-11,23-dimethyl3,7,15,19- tetraazatricyclo-[19.3.1.18 19,13,21] heptacosa-1(24),2,7,9,11,13(26), 14,19,21(25),22-decaene-25,26-diolate) and of its dicopper(II) precursor [Cu2L(H2O)2](ClO4)2 2 have been investigated by cyclic voltammetry and controlled potential electrolysis in different organic solvents. They exhibit two consecutive reversible one-electron reductions assigned to the CuII CuII → CuI CuII → CuI CuI cathodic processes. The results suggest that, in solution, phenanthroline does not coordinate to the metal in complex 1, but its H-bonding interaction with the water ligands can be preserved.